Reproducible mesoporous silica-coated gold@silver nanoprobes for the bright colorimetric sensing of ascorbic acid. (24th June 2019) - Chen, Ling; Lin, Meng; Yang, Ping
Abstract : Herein, a colorimetric approach for the detection of ascorbic acid (AA) was developed by controlling the surface chemistry of silica-coated gold nanorod@silver nanoparticles (AuNR@Ag@mSiO2 ). Abstract : Herein, a colorimetric approach for the detection of ascorbic acid (AA) was developed by controlling the surface chemistry of silica-coated gold nanorod@silver nanoparticles (AuNR@Ag@mSiO2 ). The mesoporous silica coating exhibits an elastic feature and provides a stable microenvironment around the AuNR@Ag nanoparticles. The sensing strategy was assisted by permanganate (MnO4 − ), a strong oxidizing agent, via the oxidation of silver atoms to silver ions; this resulted in the disappearance of the particle shell. The absence of the silver shell caused a color change and red shift of the UV-Vis absorption band of the colloidal solution. On the other hand, the presence of AA molecules reduced the silver ions and restored the silver shell; this was associated with the recovery of the original morphology, a color change and a red shift in the absorption band. The removal and re-growth of the Ag shell on Au NRs drastically affected the localized surface plasmon resonance (LSPR) property, which provided a strategy for the colorimetric detection of AA. A good linear relationship was obtained with a low detection limit (0.03 μM), and the method was successfully used to detect AA in serum with the satisfactory recovery of 93.8–104.5%. Furthermore, due to the removal and re-growth of the silver shell, the proposed sensor exhibits excellent reversibility and potential for practical applications.